Disclosure patterns in derivatives reporting by UK firms: implications for corporate governance. (17th December 2007) - Dunne, Theresa; Fox, Alison; Helliar, Christine
This paper provides a description of an empirical investigation into the disclosure of information concerning the use of derivatives and other financial instruments in corporate annual reports of UK firms following the introduction of Financial Reporting Standard 13 (FRS 13) 'Derivatives and other financial instruments ? disclosures'. The results indicate that the implementation of this standard was associated with a substantial increase in derivatives-related information available in corporate annual reports. It is argued that this increase in disclosure has implications for the corporate governance and internal control mechanisms of the reporting companies.